Association between Polymorphism of β-Lactoglobulin Gene on Milk Yield and Quality in Local Sheep at Jonggol Animal Science Teaching and Research Unit (JASTRU) - Sumantri, Cece; D, Nurhayati; Farajallah, Ahmad; Anggraeni, A (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2008)
The aims of this study were to identify the effects polymorphism of β-lactoglobulin gene on milk yield and percentage of milk protein and fat in local sheep. A total number of 83 heads of lactating ewes raised under an extensive management at Jonggol Animal Science Teaching and Research Unit (JASTRU) of the Faculty of Anima Science, Bogor Agricultural University were studied. Research activities were carried out through some step involving blood collection. DNA isolation, DNA amplification and separation of DNA fragments by electrophoresis with silver staining method. By using polymerase chain reaction (P R) then genotyped by single strand conformation polymorphism technique (SSCP), it was success fully amplified a fragment length at 420 bp in β-lactoglobulin gene located on the exon 7. The electrophoresis pattern revealed 5 types of β-lactoglobulin gene and designated as AB. C, D and E types. The proportion for those respective 5 type from the highest to the lowest were for A (27.7%)C (16.87%), D (12.05%), (10.84%) and B (9.64%) respectively. There were no significant effect polymorphism β-lactoglobulin gene on both milk yield and quality in I cal sheep at JASTRU. Keywords : polymorphism. β-lactoglobulin in gene, PCR-SSCP and local sheep